Effects of Dormancy-Breaking Treatments on Seed Quality Parameters in Medicinal Herb Tulsi (Ocimum tenuiflorum L.) - SULTAN SINGH; AXAY BHUKER; SANDEEP KUMAR; AMIT KUMAR; ANIL KUMAR DHAKA (Seed Research, 2026)
Tulsi, holds a revered status in various cultures around the world for its medicinal, culinary, and spiritual significance. This study was conducted for optimizing the germination test and seed quality parameters at alternate temperature of 20-30°C in Tulsi during 2022 in the laboratory of Department of Seed Science and Technology, CCS HAU Hisar. Various dormancy-breaking treatments were used during the study such as, GA3 @ 0.05 and 0.1% for 24 hours, KNO3@ 0.2% for 24 hours, Pre-chilling (5-10oC for 7 days), and Light treatments (16 hours light followed by 8 hours darkness). The results revealed that the germination percentage, seedling length, seedling dry weight, vigour index-I and vigour index-II was recorded maximum in top of the paper (TP) with the GA3 0.1% treatment and the minimum was recorded with control in sand substrate at 20-30oC alternate temperature. The radicle emergence was recorded maximum with GA3 @ 0.1% at 7th day at 20-30oC alternate temperature. The dormant seeds were observed maximum with control in BP and the minimum dormant seeds were recorded with GA3 0.1% in TP at 20-30oC alternate temperature. The research reveals significant effects of these treatments on seed germination and other crucial seedling parameters. Seeds treated with GA3 0.1% exhibited substantial improvements in germination percentage and overall seedling quality. These findings highlight the efficacy of GA3 treatment in enhancing the germination process and seedling establishment of Tulsi under specified temperature conditions.